Damage evaluation of sandwich material on side plate hull using experimental modal analysis. (2021) - Ariesta, R.C.; Zubaydi, A.; Ismail, A.; Tuswan, T.
Abstract: Sandwich material is a material innovation that is applied widely. One example is the sandwich material in ship construction. The application of the sandwich material provides the advantages of reduced weight and toughness under impact loads. In the development of this material can be damaged. The majority of damage that occurred in the core of the material was hard to identify. In this study, the identification of damage evaluates by testing the sandwich material on a laboratory scale. The damage was evaluated by experiments modal analysis (EMA). This technique uses a vibration base to determine damage to the material. Damage indicators detect when there is a natural frequency decrease in the frequency of the sandwich material.